Morgan McWilliams: capstone - McWilliams, Morgan, artist (Colorado State University. Libraries, 2024)
The artist's statement: My name is Morgan McWilliams, and I am a Graphic Designer studying at Colorado State University. As a graphic designer, I work mostly digitally through Adobe creative suites, however, I find myself exploring traditional pen and paper drawings to give my pieces a more personalized feeling. I am very passionate about typography whether it is through logo designs, magazines, business re-brands, or book designs. I also have a passion for illustration, but this work is more exploratory as I am working on being more comfortable with this side of graphic design. Even though my work spans many different types of projects, I am very inspired by minimalist and clean designs. With this, I also find myself drawn to delicate practices such as watercolor, fine line drawings, and I primarily use delicate colors such as earth tones and pastels. Ever since I was young, I have loved art. I recall myself sitting in front of my TV as a kid drawing fine line pictures of random objects. Ironically, this is still the type of art I make. For one of my projects from 2023, I created a National Geographic Kids magazine using only fine line drawings of different space objects. In my most recent project, a poster for the opera "Romeo et Juliette," I drew different elements from the story using a fine tip marker and scanned them into Adobe Illustrator using Adobe Capture and created a pattern with them. I enjoy this type of work because it is minimalist which can ultimately make the piece feel quiet, which is exactly the feeling I wanted people to feel when looking at these two works. It is important for me to capture a feeling within every project I create because I want the viewer to experience the piece with more than just their eyes. This feeling of quietness is not a common theme throughout my pieces, but it is something I have been exploring recently.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design